Just Debt : Theology, Ethics, and Neoliberalism - Ahn, Ilsup (Book collections on Project MUSE., 2017)
" ... We [have] come to have a delimited and skewed view on debt and its economy ... In this book, I argue, a more holistic social ethics of debt is established by reintegrating these two essential elements of debt: logic and story. From the perspective of a more holistic ethics of debt, neoliberal concept of debt is problematic because by neglecting the story aspect of debt, it has enervated the moral ethos of debt rendering it as a matter of mere contract and mechanical calculation"--Introduction.